The Use of Radio Podcast in Teaching Listening Comprehension at STKIP PGRI Tulungagung - Willy Anugrah Gumilang (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2020)
For EFL learners, listening comprehension is often considered as one of the most difficult skills. Consequently, it is really hard for the EFL students to achieve the good mark. Lee and Hatesohl (1993) state that in our waking hours, people spend 9 percent writing, 16 percent reading, 30 percent speaking, and 45 percent listening. There are many kinds of media that can be used to learn English: audio, visual, and audio visual media. Here, the discussion focuses on the audio media applied in teaching listening skill to the first semester students through the use of radio podcast at STKIP PGRI Tulungagung.The writer presents conceptual study by highlighting the use of radio podcast in teaching listening which is assumed more practical than other media. This condition includes all English lecturers who also busy themselves with the improvement of teaching skill. One of the innovative media used by lecturer is radio podcast. Baehaqi (2011:21) states radio podcasts are existing radio programs turned into podcasts, such as BBC News. The English lecturer uses radio podcasts which include audio materials then given to the students. By giving up-to-date materials through an attractive media, the atmosphere of listening class has become exciting activity.